Bronchodilator effect on regional lung function in pediatric viral lower respiratory tract infections. (28th October 2022) - Strodthoff, Claas; Kähkönen, Toni; Bayford, Richard H; Becher, Tobias; Frerichs, Inéz; Kallio, Merja
Abstract: Objective. Viral lower respiratory tract infections (LRTI) are the leading cause for acute admission to the intensive care unit in infants and young children. Nebulized bronchodilators are often used when treating the most severe cases. The aim of this study was to investigate the bronchodilator effect on respiratory mechanics during intensive care with electrical impedance tomography (EIT) and to assess the feasibility of EIT in this context. Approach. We continuously monitored the children with chest EIT for up to 72 h in an observational study design. The treatment decisions were done by clinical assessment, as the clinicians were blinded to the EIT information during data collection. In a retrospective analysis, clinical parameters and regional expiratory time constants determined by EIT were used to assess the effects of bronchodilator administration, especially regarding airway resistance. Main results. We included six children from 11 to 27 months of age requiring intensive care due to viral LRTI and receiving bronchodilator agents. Altogether 131 bronchodilator administrations were identified during EIT monitoring. After validation of the exact timing of events and EIT data quality, 77 administrations were included in the final analysis. Fifty-five bronchodilator events occurred during invasive ventilation and 22 during high-flow nasal cannulae treatment. Only 17% of the bronchodilator administrations resulted in a relevant decrease in calculated expiratory time constants. Significance. Continuous monitoring with EIT might help to optimize the treatment of LRTI in pediatric intensive care units. In particular, EIT-based regional expiratory time constants would allow objective assessment of the effects of bronchodilators and other respiratory therapies.